Assessing Medical Students’ Perceptions of High-Fidelity Psychiatric Simulation - Sita Shah; Gabrielle Sanders; Anita Stowell; Lucy Evans (BJPsych Open)
Aims: The use of high-fidelity simulation in psychiatry remains under-utilised. We aimed to evaluate the impact of high-fidelity psychiatric simulation on final-year medical students at two UK medical schools using a mixed-methods approach.